Pengaruh Motivasi Belajar Terhadap Hasil Belajar Siswa Setingkat Sekolah Menengah Pertama - Muhammad Ali Wafa; Masfufah Masfufah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This study aims to determine the effect of learning motivation on learning outcomes of students at the Junior High School (SMP) level. Learning motivation is an important factor that can encourage students to be more active, focused, and responsible in the learning process. The method used in this study is a quantitative method with a correlational approach. Data were obtained through a learning motivation questionnaire and documentation of student learning outcomes. The results of the analysis showed that there was a positive and significant relationship between learning motivation and student learning outcomes. Students with high levels of motivation tend to get better academic grades compared to students with low motivation. This finding shows that efforts to increase learning motivation, both through interesting learning strategies and support for a conducive learning environment, are very important in improving student learning achievement.